Alma Ata: Reflections and future prospects in family health strategy - Marcia MARINHO; Sonia GROISMAN (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT The International Conference on Primary Health Care, held in Alma Ata, was one of the most significant public health events in the world, where for the first time the dependency between poverty and health status was discussed and measured. Even after 40 years of its implementation, it continues to influence directly public policies related to the principles of primary care. The aim of the present study was to carry out a review of literature based on PubMed / Medline, Virtual Health Library (BVS / Bireme / WHO-PAHO) and institutional documents of Brazilian Ministry of Health, in order to point out reflections of perceptions about Alma Ata Conference, in Brazilian public policies, tracing an evolutionary profile to the family health strategy and its future perspectives. Although the study found a strong influence of the Alma Ata Conference in Brazilian public health policies it still needs improvement to reach the global goals and objectives agreed by all countries in Alma Ata and reaffirmed in the World Health Organization's 2030 Sustainability Agenda.